Consumption indexes and use of artificial diets and mullberry leaves by early instars of Bombyx mori L. (Lepidoptera: Bombycidae) - De Bortoli, Sergio Antonio; Takahashi, Roque; Vacari, Alessandra Marieli; De Bortoli, Caroline Placidi; Ramalho, Dagmara Gomes; De Bortoli, Sergio Leandro Placidi (Comunicata Scientiae, 2015)
Despite all the benefits that an artificial diet can make to the Bombyx mori rearing, as labor savings, greater production efficiency, raising during creating unfavorable conditions, and rearing virtually free of diseases, was not yet developed an adequate artificial diet for all larval stages. However , in Japan the use of artificial diets is highly diffused to rearing first and second instars silkworm larvae, covering about 50 % of the productions. The objective of this study was to determine the effects of offering artificial diets in the early instars on the consumption of natural diet and metabolism in late instar larvae of B. mori. Three types of treat systems were tested: (i) artificial diet adapted from Miao & Jiang for the first larvae instar and natural diet for others instars; (ii) similar to the previous system, differing from it by the adapted Miao & Jiang diet have been offered to larvae of first and second instars; (iii) artificial diet adapted from Sadiq for the first larvae instar and natural diet for others instars; and (iv) natural diet for all larval instars (check). As natural diet it was used fresh mulberry leaves of the hybrid ‘Shima-Miura”, that was offered five times a day. Consumption and metabolism of fifth instar larvae (late larval stage) were studied by assessing: relative consumption rate, the relative metabolic rate, relative growth rate, efficiency of conversion of ingested food into biomass; conversion efficiency the food digest into biomass; and approximate digestibility. No significant effect of feeding treatment systems was observed in any biological parameter studied, indicating that the supply of artificial diets Sadiq for the first instar larvae, or Jiang & Miao diet for the first and second instars larvae, were not affecting the consumption of natural diet and metabolism of fifth larvae of B. mori, showing that they can be incorporated into a silkworm food system.